IMF involvement in international trade policy issues: evaluation update 2019 - International Monetary Fund. Independent Evaluation Office (Washington, D.C International Monetary Fund (IMF), 2019)
The Independent Evaluation Office (IEO) completed an evaluation of IMF Involvement in International Trade Policy Issues in 2009. The evaluation was published at a time when global trade was experiencing a historically unprecedented decline in the wake of the global financial crisis (GFC). This report updates the IEO’s 2009 study, covering the period from January 2010 to August 2019, examining the Fund’s reaction to the myriad developments that have reshaped the global trade system (GTS) over the last decade. (IMF page)
​Executive summary -- 1. Introduction -- 2. THE 2009 Evaluation: key findings and recommendations -- 3. international trade and trade policy issues: a decade of change -- 4. Ten years of IMF trade-related work: an assessment -- 5. Conclusions, challenges, and opportunities
​Includes bibliographical references (P: 39-41)
Keywords: International Trade; INTERNATIONAL TRADE; INTERNATIONAL COOPERATION; COMMERCIAL POLICY; IMF; EVALUATION